The History of Lithuanian Journalism in the Works of Lithuanian Americans - Raguotis, Bronius (Žurnalistikos tyrimai, 2017)
This is the second part of author research about the history of Lithuanian journalism in the works of Lithuanian Americans. The first article was published in 2008. In the second part, the author makes an analysis of period 1905–1919 and compare it with the period of 1879–1904 analysed in the first article.